Transurethral Incision of the Bladder Neck at Three Points with a Needle-Type Electrode for Bladder Neck Contracture - Cao, Guihua; Liu, Liangcheng; Du, Jianping; Li, Wei; Li, Qiang; Luo, Na; Liu, Xun; Zhou, Junjie; Wu, Tao (Frontiers in Surgery, 2022)
Purpose This study aims to evaluate the efficacy of transurethral incision of the bladder neck (TUIBN) at three points with a needle-type electrode for treatment of bladder neck contracture (BNC). Materials and Methods Between January 2016 and April 2021, the bladder necks of 53 patients with BNC after surgery were incised by the needle-type electrode at the 5, 7, and 12 O’clock positions. Patient’s preoperational characteristics, peri- and postsurgical outcomes, such as time of operation, postoperative bladder irrigation, and postoperative hospital stay, and data of the international prostate symptom score (IPSS), maximum flow rate (Qmax), and postvoid residual (PVR) were recorded 3 and 6 months after surgery. Results All 53 cases of BNC were successfully treated in 35.00 (25.00, 45.00) min with 18.00 (14.00, 21.00) h for postoperative bladder irrigation with little intraoperative bleeding (less than 50 mL). The postoperative hospital stay ranged from 2 to 8 days, a mean of 3.50 (3.00, 5.00) days. No major intraoperative or postoperative complications were observed. All cases that underwent follow-up assessment at 3 and 6 months after the surgery showed significantly decreased IPSS and PVR and increased Qmax compared to preoperation ones (p ≤ 0.001). Of these 53 patients, there was no recurrence in severe BNC patients, but 5 of 53 (9.4%) BNC patients developed BNC again within 6 months and required repeated TUIBN. Thirty patients comprised five recurrent cases with a follow-up period of more than 1 year. Conclusions TUIBN at three points provides a safe, effective, and reliable option in treating patients with BNC.